Examining How Familiarity, Location, and Food Quality Influence Legendary Restaurant Revisit Intentions - Kristiana, Yustisia (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2025)
Customers’ willingness to revisit a restaurant generally arises from positive impressions of their previous dining experience, as well as the desire to recommend the place to others. Factors such as familiarity, location, and food quality have been found to contribute to strengthening revisit intention. This descriptive quantitative research investigated how familiarity, location, and food quality influence the revisit intention of legendary restaurants. The study involved 100 respondents who had visited legendary restaurants in West Jakarta, recruited through the distribution of structured questionnaires. The collected data were analyzed using partial least squares structural equation modeling (PLS-SEM) to assess the relationships among the studied variables. The research findings showed that familiarity and food quality exerted significant positive effects on revisit intention, while the location factor did not exhibit a significant influence. Furthermore, food quality emerged as the most dominant factor affecting revisit intention compared to familiarity. These findings suggested that while location may not be a determining factor, maintaining high food quality and increasing familiarity could significantly encourage customers to revisit legendary restaurants. The practical implication of this study is that owners and managers of legendary restaurants should invest in strategies to enhance familiarity and ensure consistently high food quality to foster stronger revisit intentions among customers